Islam di Bolaang Mongondow Utara, Sulawesi Utara: Dinamika Islamisasi di Kerajaan Kaidipang Besar dan Bintauna Abad ke-7-19 M - Tungkagi, Donald Qomaidiansyah (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2019)
The position of North Bolaang Mongondow is very strategic for trade routes as a former coastal kingdom region. Even this area is included in the spice routes to Maluku as the center of the Islamic kingdom in the eastern archipelago. The dynamics of Islamization in North Bolaang Mongondow occur through various channels of Islamization, the most striking is the influence of the trade route in the Sulawesi Sea region and its relations with the tetanga kingdoms, especially the Sultanate of Ternate. Unlike other regions, Catholicism became the religion of the kings in the North Bolaang Mongondow region before the entry of Islam. The important dynamics of Islamization in North Bolaang Mongondow are: in the beginning Islamization in the North Bolaang Mongondow region was bottom up, and from the 17th to the 19th centuries it was structured in the bureaucracy of the royal government (top down). This paper is a historical writing, using the historical method; heuristics, criticisms, interpretations, and historiography that are qualitative-analysis and are able to show a series of Islamization processes that took place in North Bolaang Mongondow in the 17th century to the 19th century. The results of this study indicate that the influence of Islam begins with the trade network in the Sulawesi Sea region, for traders who connect to Maluku as a pattern of Islamization. This network has an impact on social change in North Bolaang Mongondow which occurred in the 17th century until the 19th century since the first time Islam’s encounter with the kingdoms in the northern coast of the Sulawesi Sea peninsula was tracked.Keywords: Islamization, Sulawesi Sea, Kaidipang Besar, Bintauna, North Bolaang Mongondow Sebagai wilayah bekas kerajaan pesisir, posisi Bolaang Mongondow Utara sangat strategis untuk rute perdagangan. Bahkan wilayah ini termasuk dalam jalur rempah-rempah (spice routes) menuju Maluku sebagai pusat kerajaan Islam di bagian timur Nusantara. Dinamika Islamisasi di Bolaang Mongondow Utara terjadi melalui berbagai saluran Islamisasi, yang paling mencolok adalah pengaruh jalur niaga di kawasan Laut Sulawesi dan serta hubungan dengan kerajaan-kerajaan tetanga, terutama Kesultanan Ternate. Berbeda dengan daerah lain, agama Katolik menjadi agama raja-raja di wilayah Bolaang Mongondow Utara sebelum masuknya Islam. Dinamika Islamisasi di Bolaang Mongondow Utara yang penting dicatat diantaranya: pada mulanya Islamisasi di wilayah Bolaang Mongondow Utara melalui jalur bawah (bottom up), dan sejak abad ke-17 hingga abad ke-19 terstruktur dalam birokrasi pemerintahan kerajaan (top down). Tulisan ini merupakan tulisan sejarah, dengan menggunakan metode sejarah; heuristik, kritik, interpretasi, dan historiografi yang bersifat analisis-kualitatif dan mampu menunjukkan satu rangkaian proses Islamisasi yang terjadi di Bolaang Mongondow Utara abad ke-17 hingga abad ke-19. Hasil kajian ini menunjukkan bahwa pengaruh Islam diawali dari jaringan perdagangan di kawasan Laut Sulawesi, bagi pedagang yang menghubungkan ke Maluku sebagai satu pola Islamisasi. Jaringan ini memberi dampak terhadap perubahan sosial di Bolaang Mongondow Utara yang terjadi pada abad ke-17-19 M.Kata kunci: Islamisasi, Laut Sulawesi, Kaidipang Besar, Bintauna, Bolaang Mongondow Utara